2021
DOI: 10.3390/ijms221810048
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids—A New Perspective in Adjuvant Therapy for Pulmonary Hypertension

Abstract: Currently, no treatment can completely cure pulmonary hypertension (PH), which can lead to right ventricular failure and, consequently, death. Therefore, searching for new therapies remains important. Increased resistance in pulmonary circulation is mainly caused by the excessive contraction and proliferation of small pulmonary arteries. Cannabinoids, a group of lipophilic compounds that all interact with cannabinoid receptors, exert a pulmonary vasodilatory effect through several different mechanisms, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 89 publications
(237 reference statements)
0
4
0
Order By: Relevance
“…In our study, we have shown for the first time the overexpression of CB 1 -Rs and CB 2 -Rs in PH. Increased CB 2 -R density in lung tissue is probably associated with the presence of numerous inflammatory cells known to express CB 2 -Rs to a great extent [ 6 , 13 ]. Moreover, it has been suggested that TNFα and IL-1β can directly upregulate CB 1 -Rs and CB 2 -Rs in human blood [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we have shown for the first time the overexpression of CB 1 -Rs and CB 2 -Rs in PH. Increased CB 2 -R density in lung tissue is probably associated with the presence of numerous inflammatory cells known to express CB 2 -Rs to a great extent [ 6 , 13 ]. Moreover, it has been suggested that TNFα and IL-1β can directly upregulate CB 1 -Rs and CB 2 -Rs in human blood [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The endocannabinoid system seems to play a role in PH, although it is not entirely clear how significant it is. In our previous work, [ 15 ] we have shown that N -arachidonoyl glycine (NAGLy) and palmitoleoyl ethanolamide (POEA) levels are reduced in the lung tissue of rats with MCT-induced PH, and NAGLy is an endocannabinoid with systemic vasodilating potential [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabidiol (CBD) is a non-intoxicative phytocannabinoid with many beneficial properties including antioxidant, anti-inflammatory, and anti-fibrotic [ 11 ]. It has been demonstrated that CBD, alleviates MCT-induced PH in rats [ 9 , 12 ] and Sugen + hypoxia-induced PH in mice by reducing RV systolic pressure (RVSP) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Южно-Российский журнал терапевтической практики South Russian Journal of Therapeutic Practice 2023;4(3):[27][28][29][30][31][32][33][34][35] …”
unclassified